Factors Affecting Students’ Decisions Choosing SMA Maitreyawira Batam - Emi Lestari (STKIP Singkawang, 2017)
This study examines the quality of service that includes variable Reliability, Responsiveness, Assurance, Empathy and Evidence Direct (Tangible) partially and simultaneously affect the decision of students to choose SMA Maitreyawira Batam. The method of multiple regression analysis used by the researcher is to know and examine how big influence of independent variable which numbers two or more. Multiple regression analysis is used to know the influence of independent variables on dependent variable. The number of samples of this research is 110 students of SMA Maitreyawira Batam. The result of the research shows that there is significant influence of service quality with variable of reliability, responsiveness, assurance, empathy and tangible to student decision to choose SMA Maitreyawira Batam.